2021
DOI: 10.3390/ijerph18030950
|View full text |Cite
|
Sign up to set email alerts
|

The Motivation Journey: A Grounded Theory Study on Female Cancer Survivors’ Experience of a Psychological Intervention for Quality of Life

Abstract: Psychological interventions are proposed to cancer survivors to support their quality of life against the emotional trauma of cancer and the side effects of treatment. Psychological interventions often require patient engagement and commitment to activities that could be more or less demanding in terms of lifestyle change (e.g., psychotherapy, sports). Analyzing participant motivations (personal aims, expectations, needs) prior to participation is useful to predict their adherence to the intervention as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…It is possible to suggest that in the "Pink is Good" program an important role was played by social connections and support, peer influence and the group experience, as corroborated by qualitative research on the same project that highlighted how the social components of the program played a fundamental motivational role to participants' engagement (Durosini et al, 2021a). Despite the limitations, the participants were able to interact and share their experiences with cancer, survivorship and everyday life, and often they reported (as brief comments on the intervention experience) the social and friendship opportunities as the main factor among their take-home benefits.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It is possible to suggest that in the "Pink is Good" program an important role was played by social connections and support, peer influence and the group experience, as corroborated by qualitative research on the same project that highlighted how the social components of the program played a fundamental motivational role to participants' engagement (Durosini et al, 2021a). Despite the limitations, the participants were able to interact and share their experiences with cancer, survivorship and everyday life, and often they reported (as brief comments on the intervention experience) the social and friendship opportunities as the main factor among their take-home benefits.…”
Section: Discussionmentioning
confidence: 96%
“…Relevant indexes of participants' quality of life (depression and anxiety) or participants' commitment to healthcare management and the intervention itself (self-efficacy and satisfaction with group therapy) appeared related to the perceived quality of the peer group, created by the participants and enriched during the intervention months. It is possible that both sport activities and group cohesion would obtain significant effects within an intervention more extended in time, similar to how "Pink is Good" was originally conceived before the COVID-19 related alterations, as previous research reports that peer relationships and the building of novel social support resources can promote participants' motivation and health outcomes (Queen et al, 2017;Chen and Zhao, 2020;Durosini et al, 2021a). This is consistent with research showing that support groups may be more welcomed and beneficial to breast cancer patients if proposed and described in innovative ways (Green et al, 2018), for example as sport groups that will share self-empowering activities.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The study of Charandabi et al states that responsibility is associated with self-efficacy and emphasizes that responsibility is one of the characteristics of self-efficacious individuals [ 41 ]. A grounded theory study on female cancer survivors' experience of a psychological intervention for quality of life conducted by Durosini et al showed that not only physical health but also self-actualization is one of the most important motivational reasons for healthy behaviors such as exercise [ 42 ].…”
Section: Discussionmentioning
confidence: 99%